Tools for Institutional, Political, and Social Analysis of Policy Reform : A Sourcebook for Development Practitioners - World Bank (Washington, DC: World Bank, 2012)
This Sourcebook deals with social analysis in policy reform, encompassing the transition from gaining a better understanding of the distributional impacts of proposed or continuing reform to influencing a more informed and locally embedded process of policy review and design. In a generic sense, the term "social analysis" encompasses institutional, political, and social analyses. These three overlapping areas, derived from different disciplinary backgrounds, focus on the rules and relations that underpin and influence reform outcomes: Institutional analysis looks at the rules that people develop to govern group behavior and interaction in political, economic, and social spheres of life. Institutional analysis is based on an understanding that these rules-whether formally constructed or informally embedded in cultural practice-mediate and distort, sometimes fundamentally, the expected impacts of policy reform. Political analysis looks at the structure of power relations and often-entrenched interests of different stakeholders that affect decision making and distributional outcomes. Political analysis is built on recognition that political interests underpin many areas of policy debate and economic reform, challenging assumptions about the technical nature of policy making. Social analysis looks at the social relationships that govern interaction at different organizational levels, including households, communities, and social groups. Social analysis is built on an understanding of the role of social and cultural norms in governing relationships within and between groups of social actors, with implications for the degree of inclusion and empowerment of specific social groups.